2021
DOI: 10.1093/cdn/nzab095
|View full text |Cite
|
Sign up to set email alerts
|

Season of Data Collection of Child Dietary Diversity Indicators May Affect Conclusions About Longer-Term Trends in Peru, Senegal, and Nepal

Abstract: Background The WHO-UNICEF minimum dietary diversity (MDD) indicator for children aged 6–23 months is a global monitoring indicator used to track multi-year population-level changes in dietary quality, but the influence of seasonality on MDD estimates remains unclear. Objective Examine how seasonality of data collection may influence population-level MDD estimates and inferences about MDD change over multiple survey years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Indeed, low dietary diversity has been attributed to a high dependence on tô , which is a stiff, cereal-based porridge served with a watery sauce containing green, leafy vegetables (e.g., sorrel and baobab leaves) and sporadically garnished with other vegetables (e.g., eggplant, tomato, and okra) or nuts and seeds (peanuts and néré seed), with or without meat, fish, or caterpillars ( 19 , 27 , 43 ). Moreover, in parallel to our findings, vitamin A–rich fruit and vegetable consumption [e.g., ripe mangoes ( 2 )] exhibited the most seasonality among under-5 children in Nepal, Peru, and Senegal ( 8 ), which was, however, buffered slightly by a higher consumption prevalence of flesh foods and other vegetables by women enrolled in MISAME-III. In contrast, the lack of intra-annual variability in the consumption of dark green, leafy vegetables, for example, might be explained by the different seasonal harvesting patterns of species and varieties within the same FG ( 61 ) or by processing techniques (e.g., dried compared with fresh foods).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Indeed, low dietary diversity has been attributed to a high dependence on tô , which is a stiff, cereal-based porridge served with a watery sauce containing green, leafy vegetables (e.g., sorrel and baobab leaves) and sporadically garnished with other vegetables (e.g., eggplant, tomato, and okra) or nuts and seeds (peanuts and néré seed), with or without meat, fish, or caterpillars ( 19 , 27 , 43 ). Moreover, in parallel to our findings, vitamin A–rich fruit and vegetable consumption [e.g., ripe mangoes ( 2 )] exhibited the most seasonality among under-5 children in Nepal, Peru, and Senegal ( 8 ), which was, however, buffered slightly by a higher consumption prevalence of flesh foods and other vegetables by women enrolled in MISAME-III. In contrast, the lack of intra-annual variability in the consumption of dark green, leafy vegetables, for example, might be explained by the different seasonal harvesting patterns of species and varieties within the same FG ( 61 ) or by processing techniques (e.g., dried compared with fresh foods).…”
Section: Discussionsupporting
confidence: 85%
“…Hence, mismatches in the timing of repeated cross-sectional surveys might exert spurious influences on inferences about changes in the FG diversity score or MDD-W prevalence among pregnant women over time, in particular if observational studies are not conducted in the same season. Thorne-Lyman et al ( 8 ) indicated that average annual rates of change (over ∼5 years) in children's 8-point FG score and a dichotomous indicator (≥5 FGs) were not markedly larger than the average seasonal changes observed, which suggests that seasonal fluctuations are large enough to introduce bias into inferences of change and trends in dietary diversity, particularly when data collection is annual and baseline levels are high. Furthermore, in MISAME-III, a dichotomous MDD-W (i.e., only crossing >5 FGs reflects change) resulted in only a slight loss of responsiveness to seasonality among MISAME-III participants, thus leading us to conclude that changes occur mainly amongst segments of our sample with FG diversity scores close to the 5-FG cutoff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, our analysis model did not account for within-country seasonality of food availability. Types of affordable food and diversity of market-available food are season-dependent [ 59 ]. To alleviate the seasonal impacts on child’s food intake caused by various data collection periods between countries, we built a unique analysis model for each country.…”
Section: Discussionmentioning
confidence: 99%